Gestural coupling and social cognition: Möbius Syndrome as a case study - Krueger, Joel; Michael, John (Frontiers in Human Neuroscience, 2012)
Social cognition researchers have become increasingly interested in the ways that behavioral, physiological, and neural coupling facilitate social interaction and interpersonal understanding. We distinguish two ways of conceptualizing the role of such coupling processes in social cognition: strong and moderate interactionism. According to strong interactionism (SI), low-level coupling processes are alternatives to higher-level individual cognitive processes; the former at least sometimes render the latter superfluous. Moderate interactionism (MI) on the other hand, is an integrative approach. Its guiding assumption is that higher-level cognitive processes are likely to have been shaped by the need to coordinate, modulate, and extract information from low-level coupling processes. In this paper, we present a case study on Möbius Syndrome (MS) in order to contrast SI and MI. We show how MS—a form of congenital bilateral facial paralysis—can be a fruitful source of insight for research exploring the relation between high-level cognition and low-level coupling. Lacking a capacity for facial expression, individuals with MS are deprived of a primary channel for gestural coupling. According to SI, they lack an essential enabling feature for social interaction and interpersonal understanding more generally and thus ought to exhibit severe deficits in these areas. We challenge SI's prediction and show how MS cases offer compelling reasons for instead adopting MI's pluralistic model of social interaction and interpersonal understanding. We conclude that investigations of coupling processes within social interaction should inform rather than marginalize or eliminate investigation of higher-level individual cognition.